The Impact of IMF-Supported Programs on FDI in Low-income Countries - Al-Sadiq, Ali (IMF Working Papers; Working Paper, 2015)
It is common for IMF-supported adjustment programs with low-income member countries (LICs) to project that they will facilitate FDI inflows. The main objective of this paper is to empirically examine this hypothesis. Using an unbalanced panel dataset for 73 low-income countries over the period 1980-2012, and two different econometric methods that address the selection-bias problem, the empirical results robustly show that participating in IMF-supported program is associated with a significant increase in FDI inflows.